Fear of loss through Oasis’ song “Stand by Me and “Don’t go away” - Ignatius Lingga Dwantoro; M. Fadla Nur Kholbi Gifari; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research examines the portrayal of loss anxiety in Oasis’s songs “Stand by Me” and “Don’t Go Away.” Employing a qualitative descriptive approach, the study examines song lyrics as primary data to reveal how "characters' overt and covert emotions" are expressed through language. Through an analysis of connotative meanings and rhetorical techniques, the research reveals that both songs depict a deep conflict involving emotional reliance and feelings of separation anxiety. In particular, the lyrics depict a narrator's delicate "adult ability to... cultivate mental skills for self-soothing." This research suggests that popular music acts as a significant, non-clinical medium for comprehending intricate psychological experiences associated with attachment and loss.